2015
DOI: 10.1002/anie.201504903
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Fe‐N‐C Catalysts in Acidic Medium Studied by Operando Spectroscopy

Abstract: Fundamental understanding of non-precious metal catalysts for the oxygen reduction reaction (ORR) is the nub for the successful replacement of noble Pt in fuel cells and, therefore, of central importance for a technological breakthrough. Herein, the degradation mechanisms of a model high-performance Fe-N-C catalyst have been studied with online inductively coupled plasma mass spectrometry (ICP-MS) and differential electrochemical mass spectroscopy (DEMS) coupled to a modified scanning flow cell (SFC) system. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
386
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(400 citation statements)
references
References 50 publications
10
386
2
2
Order By: Relevance
“…While ORR pathways have been widely studied in both acidic [15], [16], [17], [18] and alkaline [19], [20], [21], [22] media, the kinetic mechanisms taking place in neutral media − in which MFCs usually operate − are not fully understood. Using the rotating ring disk electrode (RRDE) technique, it was recently shown that oxygen is reduced via a 2e − mechanism on carbon black and activated carbon [23], [24], where as a 4e − pathway is dominant for Pt [24] and Fe-based catalyst [25], [26].…”
Section: Introductionmentioning
confidence: 99%
“…While ORR pathways have been widely studied in both acidic [15], [16], [17], [18] and alkaline [19], [20], [21], [22] media, the kinetic mechanisms taking place in neutral media − in which MFCs usually operate − are not fully understood. Using the rotating ring disk electrode (RRDE) technique, it was recently shown that oxygen is reduced via a 2e − mechanism on carbon black and activated carbon [23], [24], where as a 4e − pathway is dominant for Pt [24] and Fe-based catalyst [25], [26].…”
Section: Introductionmentioning
confidence: 99%
“…Among the various dopants, nitrogen attracted most interest [15,[20][21][22]. and applications of transition metal/N-doped graphene (NGr) based catalytic systems ranges from oxygen reduction reactions (ORR) [23][24][25][26], hydrogen evolving reactions (HER) [27,28], photocatalysis [29,30], oxidation [31][32][33][34][35][36][37][38], and reduction [39][40][41][42][43][44] reactions of organic molecules, C-C bond formation [45] to many others [46][47][48][49][50][51]. Hence, merging rationally-designed suitable modified supports with cheap transition metals permits access to the design of active, selective and cheap catalytic materials thus allowing to match or to outperform noble-metal-based catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Fe-N-C catalysts have been extensively studied for oxygen reduction reaction (ORR) in acidic [28], [29], [30], [31], neutral [32], [33], [34], [35] and alkaline conditions [36], [37], [38], [39]. The materials were found to be extremely active in all pH conditions and performance was better than Pt in alkaline media [40].…”
Section: Introductionmentioning
confidence: 99%